A novel nonsense mutation in ARMC5 causes primary bilateral macronodular adrenocortical hyperplasia - Wen-Tao He; Xiong Wang; Wen Song; Xiao-Dong Song; Yan-Jun Lu; Yan-Kai Lv; Ting He; Xue-Feng Yu; Shu-Hong Hu (BMC, 2021)
Abstract Background Primary bilateral macronodular adrenocortical hyperplasia (PBMAH) is a rare form of adrenal Cushing's syndrome. The slowly progressing expansion of bilateral adrenal tissues usually persists for dozens of years, leading to delayed onset with severe conditions due to chronic mild hypercortisolism. About 20-50% cases were found to be caused by inactivating mutation of armadillo repeat-containing protein 5 (ARMC5) gene. Case presentation A 51-year-old man was admitted for severe diabetes mellitus, resistant hypertension, centripedal obesity and edema. PBMAH was diagnosed after determination of adrenocorticotropic hormone and cortisol levels, dexamethasone suppression tests and abdominal contrast-enhanced CT scanning. The metabolic disorders of the patient remarkably improved after sequentially bilateral laparoscopic adrenalectomy combined with hormone replacement. Sanger sequencing showed germline nonsense mutation of ARMC5 c.967C>T (p.Gln323Ter). The second somatic missense mutation of ARMC5 was detected in one out of two resected nodules, reflecting the second-hit model of tumorigenesis. Routine genetic testing in his apparently healthy offspring showed one of two daughters and one son harbored the germline mutation. Conclusions In conclusion, our case report highlight the importance of genetic testing in the molecular diagnosis of PBMAH. Genetic screening in related family members will find out asymptomatic variant carriers to guide life-long follow-up.